Dual‐band bandpass filter based on a single triple‐mode ring resonator. Issue 9 (6th April 2016) - Tang, Ming‐Chun; Shi, Ting; Chen, Shiyong; Cao, Hailin
Abstract : A novel dual‐band bandpass filter (BPF) based on a single triple‐mode ring resonator is proposed. The proposed BPF could provide three transmission poles for each passband to improve operating bandwidth. Meanwhile, seven transmission zeros are achieved at the stopband to improve the selectivity. The proposed dual‐band BPF was designed, fabricated and tested. The measured results are in good agreement with the simulated values.